2010
DOI: 10.1007/s11999-010-1461-y
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic and Gender Differences in the Functional Disparities after Primary Total Knee Arthroplasty

Abstract: Background The benefits of TKA have been well documented. Whether these benefits apply equally across gender and ethnic groups is unclear. Given the underuse of TKA among certain demographic groups, it is important to understand whether gender or ethnicity influence pain and function after TKA. Questions/purposes We determined (1) the influence of race, gender, and body mass index (BMI) on primary TKA functional scores and ROM before gender-specific implants; and (2) months).Results African-Americans had long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
68
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 33 publications
7
68
0
Order By: Relevance
“…Postoperatively, black patients reported more pain as measured by the VAS and worse overall quality of wellbeing (QWB-7), general health (SF-36), and diseasespecific scores (WOMAC) when compared with white patients at a followup of at least 1 year after surgery. Our results are in agreement with the ones of Kamath et al [11]. The authors found that gender and race affected functional knee scores and ROM.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Postoperatively, black patients reported more pain as measured by the VAS and worse overall quality of wellbeing (QWB-7), general health (SF-36), and diseasespecific scores (WOMAC) when compared with white patients at a followup of at least 1 year after surgery. Our results are in agreement with the ones of Kamath et al [11]. The authors found that gender and race affected functional knee scores and ROM.…”
Section: Discussionsupporting
confidence: 94%
“…Unfortunately, studies [4,9,11] often fail to address race and ethnicity as separate entities and have compared Hispanics or Latinos with blacks, whites, or other races such as Native American or Alaska Native, Asian, Native Hawaiian, or other Pacific Islander [25]. The genetic background is linked to race, whereas its expression is influenced by cultural and/or environmental factors (like ethnicity).…”
Section: Introductionmentioning
confidence: 99%
“…However, our institution provides surgical care for referrals from other institutions as well as primary orthopedic care to the local population (similar to community-based practices). The similarity of our cohort to other published studies (5052) as well as the NIS sample (6), and similarity in magnitude of increase in comorbidity to the recent NIS study (6) support our sample’s representativeness and the generalizability of these findings. We adjusted our multivariable-adjusted analyses for several important covariates, but residual confounding is possible in a cohort study.…”
Section: Discussionsupporting
confidence: 84%
“…Our overall study and the qualitative portion included few persons from racial and ethnic minority groups. We are unable to say whether our results apply to patients more marginalized or challenged in their TKA experience through language or racial or minority status [51, 52]. These results do not explore the experiences of those who never receive TKA surgery in the first place, either by their decision to not have surgery or by being less likely to be offered surgery [53].…”
Section: Discussionmentioning
confidence: 99%